Munigua, Spanien - Martini, Wolfram; Rassmann, Knut; Schattner, Thomas G.; Scholz, Roman (e-Forschungsberichte des DAI, 2023)
With more than 50 years of continous investigation by members of DAI’s Madrid Department, Munigua today belongs to the best known roman cities in the Iberian Peninsula. Large areas of the city are discovered, especially the central part with the public and sacred buildings and also some town-houses. As a result, Munigua can be considered today the largest iron producer of the Lower Guadalquivir Valley in Roman Times. The new project, started in 2012, aims at a 3D-reconstruction of the city.